2013
DOI: 10.1371/journal.pone.0079965
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and High-Intensity Interval Training: Which Promotes Higher Pleasure?

Abstract: ObjectivesTo compare the psychological responses to continuous (CT) and high-intensity interval training (HIT) sessions.MethodsFifteen men attended one CT session and one HIT session. During the first visit, the maximum heart rate, VO2Peak and respiratory compensation point (RCP) were determined through a maximal cardiopulmonary exercise test. The HIT stimulus intensity corresponded to 100% of VO2Peak, and the average intensity of both sessions was maintained at 15% below the RCP. The order of the sessions was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
133
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(161 citation statements)
references
References 31 publications
19
133
3
6
Order By: Relevance
“…Moreover, the anticipated enjoyment of performing 5:40 and 15:120 protocols for 3×/week over the next month was greater than 30:240. A rebound in postexercise affect was previously observed following HIIT protocols (Oliveira et al 2013;Jung et al 2014) and studies consistently demonstrate that HIIT/SIT are perceived as enjoyable when assessed at postexercise (Bartlett et al 2011;Oliveira et al 2013;Jung et al 2014;Kilpatrick et al 2015a;Martinez et al 2015). Taken together, because affective responses and perceived enjoyment can positively influence future exercise participation, at least during MICT (Rhodes et al 2010), future research should perform long-term training studies utilizing our reduced-duration sprint protocols to assess their potential as alternatives to traditional SIT.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, the anticipated enjoyment of performing 5:40 and 15:120 protocols for 3×/week over the next month was greater than 30:240. A rebound in postexercise affect was previously observed following HIIT protocols (Oliveira et al 2013;Jung et al 2014) and studies consistently demonstrate that HIIT/SIT are perceived as enjoyable when assessed at postexercise (Bartlett et al 2011;Oliveira et al 2013;Jung et al 2014;Kilpatrick et al 2015a;Martinez et al 2015). Taken together, because affective responses and perceived enjoyment can positively influence future exercise participation, at least during MICT (Rhodes et al 2010), future research should perform long-term training studies utilizing our reduced-duration sprint protocols to assess their potential as alternatives to traditional SIT.…”
Section: Discussionmentioning
confidence: 55%
“…When considering the role of psychological perceptions (such as affect and enjoyment) in HIIT and SIT as types of PA, results to date have been equivocal (Oliveira et al 2013;Kilpatrick and Greeley 2014;Kilpatrick et al 2015b;Saanijoki et al 2015), though some reports demonstrate greater enjoyment of HIIT compared with MICT in overweight and healthy individuals (Bartlett et al 2011;Crisp et al 2012). Interestingly, direct comparison between SIT (8 × 30 s at 130% maximal work separated by 90 s of recovery, ϳ79% age-predicted maximal heart rate) and HIIT (8 × 60 s at 85% maximal work with 1 min of recovery, ϳ77% age-predicted maximal heart rate) in young active individuals found that the affective responses were similar despite greater blood lactate concentrations and perceived exertion during SIT (Wood et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hardcastle et al [16] assert that SIT is too physically demanding for a largely sedentary population, and that low levels of enjoyment and affect elicited by the intense nature of SIT may discourage exercise adherence and motivation. However, the current study and related investigations ( [12][13][14] incorporated HIIT which has a lower metabolic perturbation than SIT. Despite significant physiological differences between these modes of interval training, findings from recent studies showed similar enjoyment between two regimes of HIIT [18] and similar affect between HIIT and SIT [19].…”
Section: Introductionmentioning
confidence: 80%
“…Previous affect research has found high intensity interval training to produce negative feeling responses in comparison to continuous training during and after exercise [28]. Conversely, greater positive affect is evident after acute bouts of moderate intensity exercise [33,36].…”
Section: Discussionmentioning
confidence: 94%